Quick Correction of a Skeletal Class III Maloclussion in Primary Dentition with Face Mask Plus Rapid Maxillary Expansion Therapy - Bedolla-Gaxiola DDS, Hilda Alejandra (2018)
Skeletal Class III is a malocclusion characterized by anterior crossbite as a result of an abnormal skeletal maxillary and mandibular base discrepancy, which involves disharmony of craneofacial skeleton and profile. The preferred management for children having skeletal Class III malocclusion with retruded maxilla and/or prognathic mandible is the use of devices that encourage the growth and anterior movement of the maxilla bone and/or restrict the exessive mandible growth. The orthopedic treatment consisting of a face mask with rapid maxillary expansion (RME) produces the most dramatic results in the shortest period of time. The purpose of this article is to review a quick correction of skeletal class III maloclussion in the primary dentition through a case example with use of a face mask plus rapid maxillary expansion therapy in a 5 year-old male patient due to a combination of retruded maxilla and protruded mandible, in primary dentition, who was treated with a Petit face mask in conjunction with a bonded RME intraoral appliance added with bite blocks. The first evident occlusal outcomes were a clockwise rotation of the mandible, a positive overjet of 3 mm, a correct overbite, a canine Class I relationship, and a bilateral flush terminal plane. After discussing the present clinical case report and the related published literature, we concluded that skeletal class III malocclusions should be treated as soon as the first clinical signs of abnormal craniofacial growth are recognized, during the first years of life.